THE COURSE OF PREGNANCY, CHILDBIRTH AND POSTPARTUM PERIOD IN WOMEN WITH UTERINE FIBROIDS - Isakulova M.M,; Ibragimova N.S,; Boboniyozova X.A, (TADQIQOTLAR, 2025)
Abstract. The authors of the work conducted a retrospective analysis aimed at studying the characteristics of the course of pregnancy and childbirth in women at risk for  miscarriage  with  uterine  fibroids.  Based  on  the  conducted  research,  the  most significant risk factors for the development of uterine fibroids are described, and the frequency of complications during pregnancy and childbirth is identified. Based on the results  obtained,  general  recommendations  for  the  management  of  pregnancy  and childbirth are given.